Juvenile Justice Systems: Poland-Brazil-Portugal - Jaron, Anna; Jaron, Anna; Janusz-Pohl, Barbara (Peter Lang, 2021)
Juvenile Justice Systems outlines options for shaping the juvenile liability models, in the form of model-patterns: the welfare model, the justice model, the rehabilitative treatment model, the restorative justice model, and different mixed models, especially the so-called (3z(B4xD formula.(3y (BThis comparative work consists of 4 parts, describing the general issues of juvenile criminal liability and characterizing three mixed models: the Polish, the Brazilian and the Portuguese. The comparison of three systems severely influenced by welfare ideas is seen as an innovative element of the presented work. The critical, theoretical analysis contributes to the reflection on the modelling of juvenile justice systems. Therefore, it may be of particular interest to legal researchers and practitioners.s